Pengembangan Budaya Literasi melalui Pojok Baca di SMP Muhammadiyah Langsa - Srimuliati, Srimuliati; Saputri, Nabila; Azzahra, Annisa; Asih, Sri; Alnisa, Siti Sayyidah; Fatrisya, Putri (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
"Reading Corner" is a literacy cultural activity carried out by students during their free time, in between classes, to read books available in the designated reading corner. Reading is a crucial activity in the teaching and learning process, as it is the skill of absorbing knowledge through textual materials. The "Reading Corner" activity is implemented as an effort to enhance students' reading interest and is applied as a habitual practice. The primary goal is to cultivate a literacy culture in the school through the creation of a reading corner in the auditorium of SMP Muhammadiyah Langsa. The establishment of the reading corner in the school's auditorium is conducted collaboratively with the students of SMP Muhammadiyah Langsa. The aim is to restore the role of the library as a center for empowering students to develop literacy-based potential. This engagement involves preparation, the promotion of the reading corner in the school auditorium, and the actual implementation of the reading corner. The outcome of this engagement is the formation of the reading corner at SMP Muhammadiyah Langsa. It is hoped that the establishment of this reading corner will contribute to the enhancement of the school's literacy culture.